Cultural Trauma – The Case of the Winner - Bretter Zoltán (Sciendo, 2020)
My study is an analysis of the emergence of the “Golden Dream” narrative in Romania, right after World War I. Along the way, I make some theoretical contributions to cultural trauma studies. ‘Winner’ and ‘loser’ are terms used to define fixed situations. Usually, only the loser (the victim, defeated) might suffer a trauma, while the occurrence of trauma is denied for the winner (the perpetrator, victor). We shall dig a little deeper and wider, demonstrating that Romania, an overall winner of WWI, will face, right after victory, a ‘cultural shock’ which has to be repressed, as part of the “Golden Dream” narrative. Through a detailed, economic, social and political analysis, I’ll be trying to argue that a shattering trauma has engendered in Romanian society; yet another addition to a whole ‘traumatic history’. The ensuing orthodox ethnonationalism takes its root from this trauma. From time-to-time, we will take a comparative glance at the trauma of the loser, particularly when we will be discussing the omissions of an otherwise seamless narrative.